c-di-AMP Accumulation Regulates Growth, Metabolism, and Immunogenicity of Mycobacterium smegmatis - Ning, Huanhuan; Liang, Xuan; Xie, Yanling; Bai, Lu; Zhang, Wei; Wang, Lifei; Kang, Jian; Lu, Yanzhi; Ma, Yanling; Bai, Guangchun; Bai, Yinlan (Frontiers in Microbiology, 2022)
Cyclic dimeric adenosine monophosphate (c-di-AMP) is a ubiquitous second messenger of bacteria involving in diverse physiological processes as well as host immune responses. MSMEG_2630 is a c-di-AMP phosphodiesterase (cnpB) of M. smegmatis, which is homologous to M. tuberculosis Rv2837c. In this study, cnpB deleted (ΔcnpB), complemented (ΔcnpB::C) and overexpressed (ΔcnpB::O) strains of M. smegmatis were constructed to investigate the role of c-di-AMP in regulating mycobacterial physiology and immunogenicity. This study had provided more precise evidences that elevated c-di-AMP level caused smaller colonies, shorter bacteria length, impaired growth, and inhibition of potassium transporter in M. smegmatis. This is the first report that elevated c-di-AMP level could inhibit biofilm formation, and induce porphyrin accumulation in M. smegmatis by regulating associated-genes expressions, which may have effects on drug-resistance and virulence of mycobacterium. Moreover, the cnpB deletion strain with elevated c-di-AMP level could induce enhanced Th1 immune responses after M. tuberculosis infection, which provided similar protection as wild type M. smegmatis against M. tuberculosis venous infection in mice model. Our findings enhanced the understanding of the physiological role of c-di-AMP in mycobacteria, and M. smegmatis cnpB deletion strain with elevated c-di-AMP level showed the potential for vaccine against tuberculosis.